2017
DOI: 10.20884/1.oa.2017.13.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry Dynamical of Siombak Lake, Medan Indonesia

Abstract: Siombak lake (28 ha area) was a salty lake located in Medan coastal, Indonesia. Water fluctuation influenced by the sea tide. Therefore, it needed to do morphometry dynamical study as the first impression of lake physical characteristic. The purpose of this study was to understand the dynamical of Siombak lake morphometry. The research was done in September 2016. Lake mapping was done by making 100 line zig zag and draw with ArcMap. Bathymetry showed that the bottom of the lake was sloping at the center part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…In addition to Mytilidae, Cerithidae is a native mangrove gastropod (estuary) that is frequent and abundant in the mangrove ecosystem (estuary) (Budiman 1991). Cerithidae molluscs were found throughout the year (Tables 4 and 5) due to the characteristics of Lake Siombak waters, which are influenced by tides from the Belawan Sea (Malacca Strait) ) (Muhtadi et al 2017), and strong currents from tides can affect the distribution and movement of molluscs in the water (Hummel et al 2016).…”
Section: Spatial and Temporal Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Mytilidae, Cerithidae is a native mangrove gastropod (estuary) that is frequent and abundant in the mangrove ecosystem (estuary) (Budiman 1991). Cerithidae molluscs were found throughout the year (Tables 4 and 5) due to the characteristics of Lake Siombak waters, which are influenced by tides from the Belawan Sea (Malacca Strait) ) (Muhtadi et al 2017), and strong currents from tides can affect the distribution and movement of molluscs in the water (Hummel et al 2016).…”
Section: Spatial and Temporal Distributionmentioning
confidence: 99%
“…Moreover, the lake is still affected by tides. The tides affect the difference in daily water level elevation and month periods (Muhtadi et al 2017;Muhtadi et al 2020a). Muhtadi et al (2020a) reported that the water level elevation ranges from −0.43 to 2.66 m during rains and −0.04 to 2.23 m during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…This study was then conducted in the Belawan estuary by observing the high and low tide conditions. The Belawan River estuary is a special and unique ecosystem with brackish waters influenced by tides (Muhtadi et al 2017;2020a). Lake Siombak is one of the tropical tidal lakes located on the coast of Medan City, North Sumatra Province, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is quite far from the sea (as far as 7.5 km from the Belawan Sea, the Malacca Strait), the tidal influence is very strong in Lake Siombak. This can be seen from the elevation of sea levels that varies according to tidal fluctuations in Belawan with a span of 2 hours in Lake Siombak (Muhtadi et al 2017a). Lake Siombak was originally a dredged area for the construction of the Belawan Medan Tanjung Morawa Toll Road (Belmera) in the mid of 1980s (Muhtadi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lake Siombak was originally a dredged area for the construction of the Belawan Medan Tanjung Morawa Toll Road (Belmera) in the mid of 1980s (Muhtadi et al 2016). However, over time the area was filled with water and formed a large puddle reaching 28 hectares (Muhtadi et al 2017a).…”
Section: Introductionmentioning
confidence: 99%